2019
DOI: 10.1371/journal.pone.0211914
|View full text |Cite
|
Sign up to set email alerts
|

White noise speech illusions in the general population: The association with psychosis expression and risk factors for psychosis

Abstract: Introduction Positive psychotic experiences are associated with increased rate of white noise speech illusions in patients and their relatives. However, findings have been conflicting to what degree speech illusions are associated with subclinical expression of psychosis in the general population. The aim of this study was to investigate the link between speech illusions and positive psychotic experiences in a general population sample. In addition, the hypothesis that speech illusions are on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Higher incidence of speech illusion has been found in patients with schizophrenia (Catalan et al, 2014; Galdos et al, 2011) and those with familial-vulnerability (Galdos et al, 2011). Speech illusion is also associated with positive psychotic symptoms in patients (Catalan et al, 2014) and children (Rimvall et al, 2016) but not in a non-clinical adult sample (Schepers, van Os, & Lousberg, 2019), and may (Galdos et al, 2011) or may not (Catalan et al, 2014) be related to positive schizotypy in non-clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…Higher incidence of speech illusion has been found in patients with schizophrenia (Catalan et al, 2014; Galdos et al, 2011) and those with familial-vulnerability (Galdos et al, 2011). Speech illusion is also associated with positive psychotic symptoms in patients (Catalan et al, 2014) and children (Rimvall et al, 2016) but not in a non-clinical adult sample (Schepers, van Os, & Lousberg, 2019), and may (Galdos et al, 2011) or may not (Catalan et al, 2014) be related to positive schizotypy in non-clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…Given that psychotic experiences and cognitive alterations are thought to reflect, in part, genetic risk for psychotic disorder (9, 40), the same underlying mechanism of gene–environment interaction may account for the dependence of patient–control and sibling–control speech illusion associations at higher levels of these traits. Thus, earlier studies have shown that in samples of the general population, no association exists between white noise speech illusions and the CAPE positive scale (17, 18). The CAPE positive scale mainly reflects alteration in delusional ideation, whereas the white noise task focuses on lower-prevalence alterations in perception.…”
Section: Discussionmentioning
confidence: 90%
“…Hypothetically, when self-reported psychotic experiences [e.g., Community Assessment of Psychic Experiences (CAPE) positive scale] and white noise speech illusions tap into the same dimension of psychotic disorder, a positive association is expected. However, in the general population, no clear association has been observed, indicating that variations of speech illusions in the general population may not signal increased risk to develop a disorder (17, 18). A finding supporting this notion is that while risk factors for subclinical psychosis expression generally correspond with risk factors for psychotic disorder (10, 11), white noise speech illusions were not associated with either childhood adversity or life events in the general population (18).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation